NILAI-NILAI AGAMA ISLAM DAN AKULTURASI BUDAYA DI WISATA RELIGI MASJID CHENG HOO PANDAAN - Wahyu Farikhatul Alfiah; Anang Sholikhudin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Religious Tourism at Cheng Hoo Mosque Pandaan is one of the religious tourism destinations known for its blend of Islamic, Javanese, and Chinese cultures. This blend is reflected not only in the mosque's architectural form, but also in the various social and religious activities carried out within its environment. This study aims to describe the Islamic religious values and the forms of cultural acculturation that develop at the religious tourism site of Cheng Hoo Mosque Pandaan. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing/verification, while data validity was tested through technical triangulation. The results show that the Islamic religious values found at Cheng Hoo Mosque Pandaan include the values of akidah (faith), ibadah (worship), and muamalah (social-economic conduct). The value of akidah is reflected in Islamic symbols within the mosque environment, the value of ibadah is manifested in various religious activities, while the value of muamalah is reflected in the social relations and economic activities of the surrounding community. The forms of cultural acculturation are seen in the blend of Islamic, Javanese, and Chinese cultural elements manifested through the building's architecture, the use of language, and socio-religious activities that take place in harmony without eliminating each culture's identity.